The gospel according to John a theological commentary - Ridderbos, Herman N.; Vriend, John (Grand Rapids, MI Eerdmans, 1997)
Includes bibliographical references and indexes.
Originally published in two volumes as "Het Evangelie naar Johannes. Proeve van een theologische Exegese", c. 1987, 1992 Uitgeversmaatschappij J.H. Kok, Kampen, the Netherlands.
Keywords: Bible. N.T. John -- theology; Bible. N.T. John -- commentaries